Jamaica : Third Review Under the Stand-By Arrangement-Staff Report; Informational Annex; Staff Supplement; and the Press Release on the Executive Board Discussion. (IMF Staff Country Reports; Country Report, 2011)
Economic developments and growth of Jamaica are discussed in this paper. Despite the good performance under the program through end-September, mounting spending pressures and delays in some fiscal reforms have required the adoption of corrective measures by the authorities. The authorities concurred with IMF staff that the potential spending overruns reflected weaknesses in expenditure management that needed to be urgently addressed. To offset the expenditure overruns, the government has adopted a number of compensatory measures.